Impact of psyho-emotional stress on the body at different periods of reproductive cycle (abstract) (Experimental biology, 2015)
In the present review, the authors consider the problem of the influence of psycho-emotional stress on the functionalstate of the human body, in particular, the possibility of stress-induced reproductive disorders and complications ofgestational period in women. The review a historical excursion problems is affected, special attention is paid to modernconcepts of physiological mechanisms regulating reactivity of women during gestation and lactation periods on thenature of the psychological and emotional stressors. Published data of endocrine regulation and possible dysfunctionsof the reproductive sphere under stress are considered. It also analyzes the material for the development of oxidativestress, which is the basis of oxidative damage of membrane structures of erythrocytes, cells of mammary gland, as aresult leads to the development of fetal abnormalities, miscarriage, low birth weight offspring, disruption of lactationand development hypogalactia.
Keywords: psycho-emotional stress; reproduction; gestation; dysfunction; oxidative stress